Identification of seven psychedelic 2, 5‐dimethoxy‐phenylethyl‐amine‐based designer drugs via benchtop 1H nuclear magnetic resonance spectroscopy. (23rd August 2021) - Araneda, Juan F.; Baumgarte, Marion; Lange, Marie; Maier, Alexander F. G.; Riegel, Susanne D.
Abstract: The dissemination of spectral information of new psychoactive substances (NPS) acquired on benchtop nuclear magnetic resonance (NMR) spectrometers is of high importance considering the emerging application of such portable and accessible instruments in forensic analyses. Seven members of the 2C‐X series (2C‐B, 2C‐C, 2C‐D, 2C‐E, 2C‐P, 2C‐T2, and 2C‐T7) of NPS were analyzed via 60 MHz 1 H benchtop NMR spectroscopy and their molecular structural relations are discussed with respect to the observed proton NMR spectra. Abstract : The molecular structural relation‐ship of seven new psychoactive substances (NPS), commonly known as members of the 2C‐X series, are discussed, and successfully differentiated with respect to the observed 60 MHz 1 H nuclear magnetic resonance (NMR) spectra. This is a step toward the development of portable forensic analyzers for on‐site NPS identification employing benchtop NMR spectrometers.